IMPLEMENTASI SUPERVISI PENDIDIKAN DALAM MENINGKATKAN KOMPETENSI GURU SMK AL KAUTSAR PURWOKERTO KABUPATEN BANYUMAS - Nuha, Muhammad Ulin; Fadhil, Muhammad Najmi; Asyari, Muhammad Musyafa (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Supervision of education is one of the efforts that can be made to improve teacher competence. High teacher competence will have a positive impact on the quality of learning. This study aims to analyze the implementation of educational supervision in improving the competence of teachers of SMK Al Kautsar Purwokerto, Banyumas Regency. This research uses a qualitative approach with a case study method. The subjects of the study were the principals and teachers of SMK Al Kautsar Purwokerto, Banyumas Regency. Data was collected through interviews, observation, and documentation. The results showed that: (1) The implementation of academic supervision is carried out by the principal once a semester, the principal also acts as a coordinator, leader, consultant, and evaluator. (2) Teacher competence is characterized by the application of pedagogic competence indicators, which include student characteristics, subject matter by the curriculum, theory, teaching modules, lesson implementation plans, syllabus, mastery of the learning process with technology, reflection, assessment, and evaluation. (3) The implementation results show that the implementation of educational supervision in improving teacher competence has run well, as evidenced by the results of the educational supervision assessment recap.